NETRALITAS MEDIA MASSA ERA KINI - Kartinawati, Erwin (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2013)
This paper is to highlight the reformation of press freedom in terms of the principle of media neutrality. Neutral, impartial or affiliated with stakeholders, and political power is one thing that is a principle in the mass media because the media must maintain its neutrality as a function of social control and educator. If the period before the reform, freedom of the press overshadowed by â€œbredelâ€ or censorship, freedom apparently it is still not fully considered in the present era. Freedom of the press is now just snatched away by its own internal media. If the first media workers have to struggle to escape from the political repression of the ruler, now media workers should strive to avoid repression owners of capital with all the interest surrounding it, in order to realize the press that truly fair and responsible. Understanding and awareness of the owners of capital or management, at least for one word and one bow to actually enforce the primary purpose of journalism, not only for profit but noble responsibility to the community that is a dream to realize a good Indonesian press.